Dissociative experiences alter resting state functional connectivity after childhood abuse - Schröder, Claudius von; Nkrumah, Richard O.; Demirakça, Traute; Ende, Gabriele; Schmahl, Christian (Scientific reports, 2025)
Dissociative experiences commonly occur alongside adverse childhood experiences (ACE), yet research on their neurofunctional biomarkers has overlooked their unique association with dimensions of childhood abuse and neglect. We investigated interactions between dissociative experiences and childhood abuse, anticipating anti-correlations between the right-lateralized anterior middle frontal gyrus (raMFG) and the medial temporal lobe, as well as the temporal gyri. Examining resting-state functional connectivity in 91 participants with a history of ACE, we employed seed-to-voxel analyses seeding the raMFG. Multiple linear regression and post-hoc moderation/mediation models explored interactions and individual effects of dissociation and dimensions of ACE. The Dissociative Experiences Scale (DES) and Childhood Trauma Questionnaire (CTQ) quantified dissociation and dimensions of ACE. A DES by CTQ-A (childhood abuse) interaction predicted an anti-correlation between the raMFG and right hippocampus, moderated by CTQ-A. The CTQ revealed negative connectivity between the raMFG and right anterior cingulate cortex. CTQ-N (childhood neglect) indicated that both the right supplementary motor area and right insula related positively to the raMFG. Our findings underscore a distinct neural signature of childhood abuse-related dissociative experiences, potentially linked to dissociated memories.